Twenty thousand leagues under the sea. - Verne, Jules 1828-1905 (Great illustrated classics, 1952)
A nineteenth-century science fiction tale of an electric submarine, its eccentric captain, and undersea world, which anticipated many of the scientific achievements of the twentieth century.